Reciprocating compressors operation & maintenance - Bloch, Heinz P., 1933- (Gulf Pub. Co., 1996)
For anyone responsible for purchasing, servicing, or operating reciprocating compressors, this book discusses the theory of operation and explains how to install, troubleshoot, overhaul, and repair all types of compressors. This broad comprehensive text offers practical details on how to purchase, service, operate, and maintain compressors used in any of the process industries such as pulp and paper, mining, food processing, pharmaceuticals.
Keywords: Compressors.; Compressors -- Maintenance and repair.; elektronické knihy; electronic books